DFT study of the role of N- and B-doping on structural, elastic and electronic properties of α-, β- and γ-graphyne. (April 2017) - Ruiz-Puigdollers, Antonio; Gamallo, Pablo
Abstract: The effects of N and B substitutional doping on α-, β- and γ-graphyne structures have been systematically considered by means of spin-polarized DFT calculations. The study is focused on describing the main changes that doping of sp 2 -and sp -C atoms produces on structural, elastic and electronic properties. Thus, the presence of N impurities contracts the carbon lattice increasing the in-plane stiffness whereas B impurities expand the lattice reducing the in-plane stiffness with respect to pure graphynes. This fact leads to harder materials or softer materials depending on doping with N or B atoms, respectively. Moreover, N and B atoms are n - and p -type dopants, respectively, that modify significantly the electronic structure of these materials. The different concentration of impurities in the lattice may lead to semiconductor-to-metal transitions, to the opening of a band gap, or to the appearance of new Dirac points (DPs) in the electronic structure, depending on the different parity of electrons or holes introduced per unit cell. The intrinsic physical properties of graphynes along with the possibility of tuning them by substitutional doping could extend their applicability as separation membranes, in transistor electronics, optoelectronics, among others. Graphical abstract: